SISTEM PENDUKUNG KEPUTUSAN PENENTUAN LAHAN KRITIS MENGGUNAKAN PREFERENCE RANKING ORGANIZATION METHOD FOR ENRICHMENT EVALUATION (PROMETHEE) - Windarto, Yudi Eko; Fathuddin, Harits; Nurhayati, Oky Dwi (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Critical land becomes a specific problem in data processing in the environmental field. Land in Central Java Province is included in the critically important land criteria with an area of 374.000 hectares. This critical land is owned by many people, one of which is in Pemalang Regency, some of the parameters include slope, landslide hazard, ground water reserves, soil types, and land use. Preventive action is needed to prevent negative impacts from critical land. Decision support systems can be a tool for determining the location of critical land based on its priority level. Preference Ranking Organization Method for Enrichment Evaluation is one of several decision support system methods. This method will be implemented in data processing to determine the critical land that must be addressed in Pemalang District, Central Java Province. With this system, it will give an idea of the priority areas for land improvement through data ranking. This system was built using PHP programming language and MySQL database. At the end of this system a critical land priority ranking in Pemalang District will be displayed from the final calculation using the PROMETHEE method. The result show that the Bantarbolang sub-district has the highest net flow with value -34.10 as the region with the highest critical land priority.
Keywords: PROMETHEE; Decision Support Systems; Critical Land; PHP; MySQL